To Evaluate the Efficiency with which Patients who have had ND-YAG Laser Capsulotomy may Reduce their Intraocular Pressure with a Predetermined Dosage of Brimonidine/Tart-Rate [0.2%] and Timalol/Maleate [0.5%] - Imran Ahmad, Jehanzeb Khan, Muhammad Zeeshan Tahir, Mubashir Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The most prevalent type of glaucoma, known as primary open-angle glaucoma (POAG), is a major contributor to preventable blindness worldwide. Treating hypertensive ocular diseases, such as elevated intraocular pressure (IOP), may decrease the development and progression of (POAG). Objective: this study was to evaluate the efficiency with which patients who have had Nd-Yag laser capsulotomy may reduce their intraocular pressure with a predetermined dosage of brimonidine tartrate 0.2% and timalol maleate 0.5% Method: From January 2022 to January 2023, a prospective, randomized trial was conducted in the Department of Ophthalmology at KMC and KTH Peshawar. Sample size 100 patients who had undergone (Nd-Yag-laser capsulotomy) were enrolled in the study. After random selection, 50 patients were divided into two groups. Group 1 received (timolol maleate) [0.5%] BID daily and Group 2 received [0.5%] (timolol maleate) in a constant proportion in addition to (0.2%) brimonidine tartrate BID daily. Intraocular pressure (IOP) was assessed at the beginning, after one week, three weeks, and four weeks. The mean IOP at 4 weeks served as the major outcome indicator. Mean IOP at 1 week, 3 week, and 4 week intervals were included as secondary end measures. Descriptive statistics, the Student’s t-test, and one-way ANOVA were used to analyse the data. Results: Mean IOP at baseline not significant with in two groups [P=0.36]. At one week, the mean IOP in the timolol group was 15.3 3.3 mmHg, compared to 13.1 2.9 mmHg in the timolol/brimonidine (P=0.001). At 3 weeks, (mean IOP) in the (timolol-group) was 14.4 3.1 mmHg, compared to 12.5 2.8 mmHg in the timolol/brimonidine group (p 0.001). At 4 weeks, the mean IOP in the timolol group was 13.8 3.1 mmHg, compared to 11.7 2.7 mmHg in the timolol/brimonidine group (p 0.001). Conclusion: this study show that persons who have had Nd-Yag laser capsulotomy benefit from a blending together timolol maleate [0.5%] and brimonidine tartrate [0.2%] to significantly reduce intraocular pressure (IOP). Keywords: Intraocular Pressure,ttimolol- maleate, brimoni-dine- tartrate, Nd-Yag Laser-Capsulotomy